COMPARISON BETWEEN MAGNETIC RESONANCE IMAGING AND ULTRASONOGRAPHY AS THE BEST EXAMINATION TO MEASURE MALIGNANT BREAST TUMORS IN SURGICAL PLANNING - Rossi, André João Rodrigues Espelho; Kluthcovsky, Ana Claudia Garabeli Cavalli; Mansani, Fábio Postiglione (Mastology, 2018)
Objective: To evaluate which examination, ultrasonography or magnetic resonance imaging, is more accurate in the measurement of malignant breast tumors in the pre-surgical evaluation, according to hormonal status. Method: This i s a d escriptive, crosssectional study in which we compared the largest tumor-size visualized by magnetic resonance imaging and ultrasonography before excision with the largest size visualized in the anatomopathological report. The sample was divided according to hormonal status: premenopausal women, postmenopausal women who have already had hormone-replacement therapy, and postmenopausal women who have never done hormone-replacement therapy. We evaluated which of the exams had a greater correlation with the size measured by the anatomopathological report using the Pearson correlation coefficient. Results: All the 39 patients had invasive-ductal carcinoma. When the total sample was analyzed (n=39), it was observed that the correlation between the ultrasonography and the anatomopathological report (r=0.73; p<0.001) was higher than the correlation between the magnetic resonance imaging and the anatomopathological report (r=0.57; p<0.001). In the premenopausal subgroup, the correlation between the ultrasonography and the anatomopathological report (r=0.46; p=0.05) was lower than the correlation between the magnetic resonance imaging and the anatomopathological report, (r=0.56; p=0.01). In the postmenopausal subgroup, Pearson’s correlation shows that ultrasonography is better at assessing tumor size than magnetic resonance imaging, regardless of hormonereplacement therapy. Conclusion: Ultrasonography is satisfactory for pre-surgical staging in invasive-ductal carcinoma, but, when available, magnetic resonance imaging may be a better indication in premenopausal patients.